Psychodermatology − biopsychosocial approach - Konstantine V. Aymedov (Kazimierz Wielki University, 2016)
Aymedov Konstantine V. Psychodermatology − biopsychosocial approach. Journal of Education, Health and Sport. 2016;6(12):941-950. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.321392 http://ojs.ukw.edu.pl/index.php/johs/article/view/4281         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016.   Psychodermatology − biopsychosocial APPROACH   Konstantine V. Aymedov   Odessa National Medical University, Ukraine psychotype@gmail.com   Abstract Cinical and psychological characteristics of psychosomatic dermatological diseases are discussed. An overview of psychodermatology historical formation as a branch of medicine dealing with mental disorders of both dermatological and psychiatric nature is done. The author emphasizes the lack of awareness among dermatologists and psychiatrists about the existence of "psychodermatology", a new rapidly developing medical direction. The most common diagnostics associated with dermal mental disorders are atopic dermatitis, psoriasis, alopecia areata, and mental disorders such as delusional parasitosis, neurotic excoriation, trichotillomania are the the most common conditions at the presence of  which dermatologists refer the patients for a psychiatrist. Only few dermatologists are ready to take liability and prescribe a psychiatric drug and make a proper psychotherapeutic support. Complex of remedial psychocorrective and psychoprophylactic measures for somatoform disorders that can be used for both general population and the patients under study is offered. Key words. psychodermatology, psychosomatic medicine, dermatology, dermatosis.